Acute Rat and Mouse Oral Toxicity Determination of Anticholinesterase Inhibitor Carbamate Pesticides: A QSTR Approach. Issue 8 (8th May 2019) - Roy, Partha Pratim; Banjare, Purusottam; Verma, Sandhya; Singh, Jagadish
Abstract: The toxic potentials of carbamates to human and non target organisms are of public concern in relation to society and ecosystem for their unregulated and indiscriminate use. No computational study was found on rat and mouse oral toxicity for carbamate pesticides. In this context, carbamate pesticides were collected from ChemIDplus databases for the modeling study. A series of local QSTR model for both rat and mouse oral toxicity of carbamate derivatives were developed according to OECD principle from 2D descriptors by using Genetic Algorithm (GA) as feature selection chemometric tools using QSARINS software. All the models indicate the importance of auto correlation descriptors related to charge, I‐State, atom type E state for fragment −O− in relation to acute mammalian toxicity. Reliability of predictions of the models was verified by applicability domain (AD) and prediction reliability index. Finally developed models were applied to unknown carbamate pesticides to evaluate their predictions and AD. The toxic nature of the prioritized compounds with structural alerts were commented in a consensus way. Additional toxicity‐toxicity relationship studies (QTTR) between these two responses with similar findings promoted further application of QTTR models in absence of one response. These findings may help the scientific community in prioritizing potentially hazardous pesticides of carbamate and related classes. Abstract :